2018
DOI: 10.1371/journal.pntd.0006685
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of dengue virus entry into myeloid cells by endocytic inhibitors in the presence or absence of antibodies

Abstract: BackgroundDengue is the most prevalent arthropod-borne viral human disease in tropical and subtropical regions, caused by four dengue virus (DENV) serotypes. In spite of the increasing global incidence, no specific antiviral therapy is available. Cells of the mononuclear phagocyte lineage are the main targets either for direct antibody (Ab)-independent or Ab-mediated human DENV infection, usually associated to the severe forms of disease. Since the virus entry may be a convenient therapeutic alternative, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…This first antipsychotic medication was discovered in 1952 by Jean Delay and Pierre Deniker at Sainte Anne hospital (2). In addition to its antipsychotic activity, a growing body of in vitro studies has demonstrated antiviral properties, for example against influenza (3), hepatitis viruses (4), alphaviruses (5), JC virus (6), Japanese encephalitis virus (7), bronchitis-virus (8), MHV-2 (9), Zika virus (10) or dengue virus (11). CPZ has also been shown to have antiviral activity against coronaviruses in multiple studies (12)(13)(14).…”
mentioning
confidence: 99%
“…This first antipsychotic medication was discovered in 1952 by Jean Delay and Pierre Deniker at Sainte Anne hospital (2). In addition to its antipsychotic activity, a growing body of in vitro studies has demonstrated antiviral properties, for example against influenza (3), hepatitis viruses (4), alphaviruses (5), JC virus (6), Japanese encephalitis virus (7), bronchitis-virus (8), MHV-2 (9), Zika virus (10) or dengue virus (11). CPZ has also been shown to have antiviral activity against coronaviruses in multiple studies (12)(13)(14).…”
mentioning
confidence: 99%
“…In vitro studies in monocytic cell lines U937 and K562 have shown that FcγRII-mediated entry occurs through clathrin-coated vesicles, while FcγRI-mediated entry is clathrinindependent. Also, as FcγRII translocates into lipid rafts upon immune complex binding, entry via this receptor is affected by the membrane cholesterol content (Carro et al 2018). In macrophage-like P388D1 cells, antibody-opsonized virus is shown to be internalized by phagocytic uptake facilitated by actin-mediated membrane protrusions which actively search and capture the antibody-bound virus particles, possible by chemotaxis (Ayala-Nunez et al 2016).…”
Section: Antibody-mediated Viral Entry Into Target Cellmentioning
confidence: 99%
“…For instance, several viruses, in particular retroviruses, can enter the cells through endocytosis and hijack and use exosomal pathways for their replication and pathogenesis [49]. Viruses such as hepatitis C virus (HCV), West Nile virus (WNV), Zika virus (ZV), and Dengue virus (DENV) enter this pathway by clathrin-mediated or receptor-mediated endocytosis [50][51][52][53][54][55][56]. Another virus that can utilize the endosomal/exosomal system for its replication and pathogenesis is the human immunodeficiency virus (HIV).…”
Section: Exosomesmentioning
confidence: 99%